Lasers based manufacturing : 5th International and 26th All India Manufacturing Technology, Design and Research Conference, AIMTDR 2014 /: 5th International and 26th All India Manufacturing Technology, Design and Research Conference, AIMTDR 2014. ([2015]) - Unknown
No abstract available